Optimalisasi Peran Keluarga dalam Mendeteksi Tumbuh Kembang Anak di Kampung KB Bina Kencana - Indrawati, Iin; Tiwi, Laida Sanilpa; Maimaznah, Maimaznah; Hidayat, Muhammad (3031-8572, 2023)
Age 0-5 years is the golden age for toddlers because there is a rapid increase in growth and development. Mother must know how important her role is in the family. The problem is that the community still lacks motivation to participate in the KB Village program, their knowledge about how to detect growth and development and recognize signs of failure in child growth and development is still lacking and the KB Village program has not been optimally followed by the community. This condition is feared to have an impact on how the mother is raised in the family, how the mother cares for, cares for and provides the nutrition needed by the child. The target of this activity is the community in Kampung KB Bina Kencana, RT 32, Lebak Village, Bandung, Jambi City. The goal is to increase the knowledge of mothers about how to detect child growth and development and signs of failure in child growth and development to prevent stunting. The implementation method is by providing health education face to face or lectures and discussions with activity participants. This activity was carried out over a period of 6 months while the implementation of providing Health Education was carried out on August 8 2023 at Kampung KB Bina Kencana RT 32, Lebak Village, Bandung, Jambi City. After the activity was carried out, it was seen that there was an increase in the knowledge of the participants as seen from the results of the post test verbally, the expressions of the community who stated they were interested in the material and were motivated to come to the next activity in the KB Village as well as statements from managers who felt helped in running the program. The activity is planned to later be published in the Sinta 5 accredited Abdimas Baiturrahim Journal.